Epigenetics evaluation of the oncogenic mechanisms of two closely related bovine and human deltaretroviruses: A system biology study. (February 2020) - Ashrafi, Fereshteh; Nassiri, Mohammadreza; Javadmanesh, Ali; Rahimi, Hossein; Rezaee, Seyed Abdolrahim
Abstract: Human T-cell lymphotropic virus (HTLV-1) and bovine leukemia virus (BLV) are oncogenic deltaretroviruses, which are the cause of adult T cell leukemia/lymphoma (ATLL) and enzootic bovine leukosis (EBL), respectively. In this study, to evaluate the virus-host interactions in the manifestation of the associated malignancy, four pooled RNA samples of each host (three RNAs in each sample) were applied to RNA-seq. Differential expression analyses were conducted separately between ATLL and EBL groups, in comparison with the healthy group, to identify functional Gene Ontology (GO) terms and hub genes, using DAVID database and MCODE plugin in Cytoscape software, respectively. A broad range of effective genes, involved in the ATLL and EBL, was up- and downregulated. In the virus side, in both malignancy, Tax was expressed very low, but the HTLV-1- HBZ and BVL- As2 transcripts were highly expressed. Some upregulated hub genes, IL2, TOP2A, MKI67, TP73, MYC, and downregulated FOS gene family ( FOS, FOSB, and FOSL2 ), are similarly activated in both human and bovine hosts, in related cell cycle and growth factors. Taken together, it seems that in preventing the infections and cell transformations, Tax must be targeted as a viral factor, and shared peptide in virological and immunological synapses as host factors. Therefore, in the malignant stages, HBZ and As2 transcripts along with growth factors, particularly IL-2R-γ and T-bet or TOP2A, and MKI67 should be targeted in both hosts. Additional studies at the protein level are necessary to elucidate the more useful targets for the therapy of these life-threatening diseases. Highlights: The manuscript is a comprehensive system biology study, using RNA-Seq technique. Introducing a broad range of effective up and downregulated hub genes, involved in ATLL and EBL malignancies. The genes  IL2,   TOP2A,   MKI67,   TP73,   MYC,   Tbx21,  and  FOS  gene family are novel target for therapy and diagnosis.. In viral side, HBZ in HTLV-1 and As2 transcript in BLV should be targeted.